2016
DOI: 10.1111/bjh.13915
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with low‐dose azacitidine for MDS in children and young adults: a retrospective analysis of the EWOGMDS study group

Abstract: Low-dose azacitidine is efficient and safe in the therapy of malignant myeloid disorders in adults but data in children are lacking. We present a retrospective analysis of 24 children and young adults with myelodysplastic syndrome (MDS) who received azacitidine at the time of first diagnosis or relapse after allotransplant (2 children were treated with azacitidine both initially and for relapse). Diagnoses were refractory cytopenia of childhood (N = 4), advanced primary MDS (N = 9) and secondary MDS (N = 11). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 13 publications
(23 reference statements)
0
19
0
1
Order By: Relevance
“…37 Our findings are consistent with a recent report of good tolerability of AZA in 24 children and young adults with different types of MDS and MDR-AML. 29 There was a trend towards higher bone marrow blast percentages at presentation in patients treated with AZA. A bias towards treating physicians favoring therapy with AZA in patients with higher blast counts at presentation cannot be completely excluded.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…37 Our findings are consistent with a recent report of good tolerability of AZA in 24 children and young adults with different types of MDS and MDR-AML. 29 There was a trend towards higher bone marrow blast percentages at presentation in patients treated with AZA. A bias towards treating physicians favoring therapy with AZA in patients with higher blast counts at presentation cannot be completely excluded.…”
Section: Discussionmentioning
confidence: 95%
“…28 The European Working Group of Myelodysplastic Syndromes in Childhood recently reported their experience with AZA in MDS and MDR-AML. 29 Their retrospective analysis comprised a heterogeneous group of children with low-grade MDS (refractory cytopenia of childhood), advanced MDS, secondary MDS, MDR-AML, and relapsed disease after HSCT. Among the seven patients with RAEB/-T in this report, only one was declared alive in remission at 24 months of follow-up; the remaining 6/7 patients died after 1-6 months.…”
Section: Response To Treatment With Azacitidine In Children With Advamentioning
confidence: 99%
“…One retrospective study showed that low-dose azacitidine for children and adolescents with MDS was safe and effective as a non-toxic option to prolong life in the palliative context [28]. Furthermore, a pilot study of 13 pediatric patients investigating the use of vorinostat and decitabine followed by a standard cytotoxic re-induction chemotherapy regimen for relapsed/refractory B-acute lymphoblastic leukemia (B-ALL) showed that the regimen was tolerable and demonstrated clinical benefit with an overall response rate of 46.2% (complete and partial response) [15].…”
Section: Discussionmentioning
confidence: 99%
“…As epigenetic changes including aberrant DNA methylation and gene silencing play an important role in the pathogenesis of AML, inhibitors such as azacitidine and decitabine have been successfully used in adult patients to treat AML and MDS without major side effects . Further, while azacitidine has been used in conjunction with DLI as salvage therapy for treatment of relapse post‐HCT in adult patients, these agents have been used only infrequently in pediatric patients . Recent studies have reported the use of fludarabine‐based regimens in patients with FA and AML for disease reduction prior to HCT .…”
Section: Discussionmentioning
confidence: 99%